2015
DOI: 10.1099/vir.0.000210
|View full text |Cite
|
Sign up to set email alerts
|

Preferential host switching and its relation with Hantavirus diversification in South America

Abstract: In recent years, the notion of co-speciation between Hantavirus species and their hosts was discarded in favour of a more likely explanation: preferential host switching. However, the relative importance of this last process in shaping the evolutionary history of hantaviruses remains uncertain, given the present limited knowledge not only of virus-host relationships but also of the pathogen and reservoir phylogenies. In South America, more than 25 hantavirus genotypes were detected; several of them act as aeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 61 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…In eastern Paraguay, Uruguay and Brazil, within the Interior Atlantic Forest (IAF), two closely related strains of hantaviruses, Juquitiba (JUQV) and Araucaria (ARAUV), associated with Oligoryzomys nigripes , have been linked to HPS cases in Brazil and Argentina [ 10 , 11 ]. Notably, the mortality associated with ANDV/JUQV and LANV differ with LANV cases showing a lower case fatality (15 versus 40% for ANDV) [ 12 15 ]. To our knowledge, no cases of HPS have been associated with Jabora virus (JABV), harbored by Akodon montensis (tribe Akodontini).…”
Section: Introductionmentioning
confidence: 99%
“…In eastern Paraguay, Uruguay and Brazil, within the Interior Atlantic Forest (IAF), two closely related strains of hantaviruses, Juquitiba (JUQV) and Araucaria (ARAUV), associated with Oligoryzomys nigripes , have been linked to HPS cases in Brazil and Argentina [ 10 , 11 ]. Notably, the mortality associated with ANDV/JUQV and LANV differ with LANV cases showing a lower case fatality (15 versus 40% for ANDV) [ 12 15 ]. To our knowledge, no cases of HPS have been associated with Jabora virus (JABV), harbored by Akodon montensis (tribe Akodontini).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent discoveries on new hosts, new viral strains, and the evolution rate of hantaviruses do not entirely support this idea (Kuhn & Schmaljohn, 2023 ). The possibility of preferential host switching has been proposed but is not supported in hantaviruses in South America, for which geographic proximity is a potential explanation of hantavirus diversification (Rivera et al., 2015 ). Using the known hantavirus hosts in Chile, we found that geographic proximity, phylogenetic relatedness, and centrality in the rodent–ectoparasite network were predictors for rodents being known hantavirus hosts.…”
Section: Discussionmentioning
confidence: 99%
“…The possibility of preferential host switching has been proposed but is not supported in hantaviruses in South America, for which geographic proximity is a potential explanation of hantavirus diversification (Rivera et al, 2015). (Lobos et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation